Uji Aktivitas Anti Inflamasi Ekstrak n-Heksan, Etil Asetat dan Etanol Daun Kecombrang (Etlingera Elatior) Pada Tikus Putih Jantan Galur Wistar (Rattus Norvegiucus) - Alfanda, Dea; Slamet; Sigit Prasojo (Universitas Muhammadiyah Klaten, 2021)
Kecombrang (Etlingera elatior) is one of the Indonesian herbal plants, frequently used by our society as anti-inflammation. This medicine has a function to reduce infection. This study aims to examine the activity of ani-inflammation from the extract of n-hexan, ethyl acetate, and ethanol of kecombrang (Etlingera elatior) leaves. It useá experimental as a method by using inflammation inhibition test on the tested white male mouse of galur wisiar as sampie. This sample is divided into 6 groups and each was given at a dose at 50 mg/kgweight, 100 mg/KGBW, 150 mg/KGBW, and 200 mg/K.gBW. Besides, for the positive control group, Diclofenac sodium was used at a dose of 4.5 mg / KGBW, which was previously induced by edema with 1% Karangenan. Edema measurenients were carried out every 10 minutes after being induced by carrageenan using a pletismometer. The data result of anti-inflammation activity from each extract has been exainined the differences between test groups with the ANOVA statistical test The result of Tukey statistical test stated ethanol extract of kecombrang leaves at a dose of 200 mg/KGBW has a good anti-inflammation activity, achieving a value of 0.972, 0.994, and 1,000. It means there is no different anong extract of n-hexan, ethyl acetate, and ethanol.